Limited evidence for the usage of renin–angiotensin–aldosterone pathway blockers to prevent arthrofibrosis after total knee arthroplasty. A systematic review of clinical evidence - Giuseppe Anzillotti; Andreas H. Gomoll; Pietro Conte; Alberto Bulgarelli; Paolo Queirazza; Maurilio Marcacci; Elizaveta Kon; Berardo Di Matteo (Journal of Experimental Orthopaedics)
Abstract Purpose Despite advances in surgical techniques and rehabilitation protocols, arthrofibrosis following total knee arthroplasty (TKA) still has poor outcomes. In the last decade, attention has been focused on the pathogenesis and cascade of events leading to the development of fibrosis. Currently, one of the most promising approaches consists in the indirect antagonisation of transforming growth factor beta 1 (TGF‐beta 1) through the downregulation of the renin–angiotensin–aldosterone system (RAAS). This systematic review aims to analyse the available evidence regarding the use of angiotensin receptor blockers (ARBs)/angiotensin‐converting‐enzyme inhibitors (ACEi) in order to prevent post‐operative knee arthrofibrosis following TKA. Methods Extensive research on the PubMed, Cochrane, and Google Scholar databases was performed on 8 July 2024, using keywords related to ARBs, ACE inhibitors and arthrofibrosis. Inclusion criteria included: (1) clinical trials of any level of evidence; (2) written in English; (3) studies conducted on humans; and (4) evaluating the antifibrotic effects of ACE inhibitors or ARBs administered for TKA surgeries. Exclusion criteria were articles written in other languages; preclinical studies; expert opinions; reviews and trials evaluating the effects of ACEi/ARBs not related to their antifibrotic effect after TKA. Results A total of six studies met the inclusion criteria and were analysed. All studies were retrospective and involved a total of 158,310 patients. Time of administration varied among the studies as well as the dosage, which fell within the range for cardiological use. Four out of six studies focused exclusively on losartan. Three studies reported a clear, significant correlation between the use of ARBs and/or ACEi and a reduced likelihood of developing arthrofibrosis. Conclusions The RAAS antagonism could have potential for stiffness prevention after TKA. However, given the side effects and the limited evidence available, the use of ACEi/sartans for the sole purpose of avoiding arthrofibrosis after TKA is not currently recommended. Level of Evidence Level III.